Effect of working capital efficiency on profitability in companies in the cigarette industry sector on the Indonesian stock exchange in the 2003-2007 period - Rachmat Anggara Supriyadi (Trigin Publisher, 2022)
The purpose of this research is to know how efficiency of working capital (net working capital turnover) can give the influence the probability (return on assets) in cigarette company which listed in the INDONESIA Stock Exchange. This research is implemented to 4 cigarette company which listed in the INDONESIA Stock Exchange from 2003-2006. The companies are PT. H.M.Sampoerna, Tbk., PT Bentoel International Investama, Tbk., PT British American Tobacco Indonesia, Tbk.,PT. Gudang Garam, Tbk. Data financial is using as the object for this research is 4 years financial statements from 2003-2006. The data of this research which have been used are secondary data with population method, analysis method like simple regression analysis method. The result of this research is to confirm that efficiency of working capital (net working capital turnover) give the influence which is significant to effect profitability (return on assets).